PENGGUNAAN METODE SYSTEM USABILITY SCALE (SUS) PADA APLIKASI SIMAMURAT - Alam, RG Guntur; Puji Rahayu Kurniasih (JSAI (Journal Scientific and Applied Informatics), 2024)
The application of an information system in a State University as an education provider is very important to obtain faster and more accurate information. One of the application systems used at Fatmawati Sukarno State Islamic University Bengkulu is the Mail Management Information System (SIMAMURAT). To determine the level of usefulness of a system / application, it is necessary to do testing. Testing can be done using the System Usability Scale (SUS) method. System Usability Scale (SUS) is one approach used to measure the level of usability or usability of a system or product based on user perception. This method was developed by John Brooke in 1986 and has become one of the standard methods in usability evaluation. The average score obtained from the calculation of SUS respondents using the SIMAMURAT application is 70.03. From these results, it can be seen that the Percentil Rank in the SIMAMURAT application is in the Good category, while the Grade in the SIMAMURAT application is C which shows the average, for Adjectives in this study it is classified as OK, while in Acceptability it is in the marginal category and for NPS classification, it is passive. From the results of this study, it can be concluded that the SIMAMURAT Application can be declared feasible based on Usability based on the SUS method.